2016
DOI: 10.1590/s1980-6574201600020011
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results on organization on the court, physical and technical performance of Brazilian professional futsal players: comparison between friendly pre-season and official match

Abstract: Abstract--The main aim of this study was to verify possible differences between a friendly pre-season match (FM) and an official in-season match (OM) regarding physical, technical, and organizational performances of a professional Brazilian futsal team. Ten professional futsal athletes participated in this study. The matches were monitored with video cameras (30 Hz) and athlete trajectories obtained with automatic tracking. The values obtained for distance covered per minute, percentage of distance covered at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 45 publications
1
16
0
2
Order By: Relevance
“…Thus, due to metabolic demand in futsal, the development of anaerobic power seems to play an important role to performance during the match; therefore, a good periodization for the specific training could be essential for this purpose. Vieira et al [35] after to compare differences between a friendly preseason match and an official in-season match regarding physical, technical, and organizational performances of a professional Brazilian futsal team, values obtained for distance covered per minute, percentage of distance covered at moderate intensity, team coverage area, spread, passes, possessions, ball touches, and successful passes per minute were greater for the official in-season match than friendly pre-season match, highlighting that after a long period of training and competitions, the team exhibited enhanced tactical and technical performances, along with enhanced physical performance, indicating a need for a good periodization during the season.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, due to metabolic demand in futsal, the development of anaerobic power seems to play an important role to performance during the match; therefore, a good periodization for the specific training could be essential for this purpose. Vieira et al [35] after to compare differences between a friendly preseason match and an official in-season match regarding physical, technical, and organizational performances of a professional Brazilian futsal team, values obtained for distance covered per minute, percentage of distance covered at moderate intensity, team coverage area, spread, passes, possessions, ball touches, and successful passes per minute were greater for the official in-season match than friendly pre-season match, highlighting that after a long period of training and competitions, the team exhibited enhanced tactical and technical performances, along with enhanced physical performance, indicating a need for a good periodization during the season.…”
Section: Discussionmentioning
confidence: 99%
“…Distance covered in high intensity running also decay in 2-H in official matches ( Barbero-Alvarez et al, 2008 ; de Oliveira Bueno et al, 2014 ). In contrast, in a simulated match the HR did not differ among the four 10-min periods ( Castagna et al, 2009 ) as well as parameters relationship to the players’ sprints did not differ between 1-H and 2-H in official matches of professional players ( Barbero-Alvarez et al, 2008 ; de Oliveira Bueno et al, 2014 ; Caetano et al, 2015 ; Vieira et al, 2016 ), friendly match ( Vieira et al, 2016 ) and simulated match ( Milioni et al, 2016 ).…”
Section: Introductionmentioning
confidence: 87%
“…The physical demand of futsal in terms of distance covered seems to be directly related to the tactical pattern performed during matches and players' technical skills [11][12][13] . According to the authors, competitive level is a variable capable of altering the tactical pattern of matches and directly influencing the intensity required in futsal matches.…”
Section: Introductionmentioning
confidence: 99%
“…In soccer, for example, it was found that the decline in physical performance during the match is not accompanied by reduction in technical actions and involvement with the ball 14 . In this sense, studies that aim to characterize the match demands and understand their interrelationships are necessary in the context of futsal 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation